Dropped in Capacity and Traffic Speed of Urban Arterial: A Case Study at U-Turn Section in Aceh Province, Indonesia - Sugiarto S; Thirayoot Limanoond; Takashi Nakatsuji (Graduate Program of Syiah Kuala University, 2012)
Abstract - Dropped in traffic capacity and travel speed during congestion were studied at a u-turn section on an arterial road in Indonesia. Traffic characteristics during congestion were analyzed using oblique cumulative plots and breakdown method. Both approaches are time series treatment between cumulative vehicles arrival versus time contracted from data recorded by video tape. Studies were conducted in both morning and evening peak hours on three regular weekdays. This study found traffic breakdown condition during the peak periods; the breakdown lasted on average 40 minutes. It was found that capacity during traffic breakdown drops in the range 8-9 percent from the before-breakdown capacity. Similarly, during the breakdown, speed drops on average 10 percent from the before condition. Several alternatives were selected and tested for improving existing conditions. It was found that adding a 50m pocket lane would help improving the existing situation by reducing the delay to 69 percent, increasing speed to 39 percent, and improving capacity to 11 percent compared to the result of simulation an existing condition